PERAN KEPEMIMPINAN DALAM STRUKTUR ADMINISTRASI PENDIDIKAN: ANALISIS FUNGSI, KOORDINASI, DAN PENGAMBILAN KEPUTUSAN - Nurul Annisa; Arismunandar (STKIP Subang, 2026)
This study aims to analyze the role of leadership in educational administration structures by emphasizing three main aspects: management functions, institutional coordination, and strategic decision-making. This study offers a contextual and empirical analysis of how school or educational institution leaders carry out their goals in directing, synergizing, and determining operational policies that impact each institution. This study presents an in-depth analysis through a qualitative descriptive approach in educational units, focusing on the interaction between leaders and work units in carrying out administrative tasks. The research findings indicate that leadership plays a strategic role in program planning, facilitating interdisciplinary coordination, and providing data- and regulatory-based decision-making. Effective leadership practices have been shown to improve work synchronization, policy accountability, operational efficiency, and a collaborative culture within educational organizations. These findings imply the need to strengthen managerial leadership capacity and develop participatory governance models within educational institutions to support sustainable quality improvement.